Impact of simple, specific, verbal instructions on the quality of bowel preparation in hospitalized patients undergoing colonoscopy: a multicenter randomized controlled trial - Triantafyllou, Konstantinos; Gkolfakis, Paraskevas; Skamnelos, Alexandros; Diamantopoulou, Georgia; Dagas, Athanasios; Tziatzios, Georgios; Thomopoulos, Konstantinos; Potamianos, Spyros; Christodoulou, Dimitrios (Endoscopy International Open, 2021)
Background and study aims Bowel preparation for colonoscopy is frequently inadequate in hospitalized patients. We explored the impact of specific verbal instructions on the quality of inpatients bowel preparation and factors associated with preparation failure.Patients and methods Randomized (1:1), two strata (mobilized vs. bedridden; 3:2) trial of consecutive inpatients from four tertiary centers, who received either specific, verbal instructions or the standard of care (SOC) ward instructions about bowel preparation. The rate of adequate bowel preparation (Boston Bowel Preparation Score [BBPS] ≥ 6, no segment < 2) comprised the primary endpoint. Mean BBPS score, good (BBPS score ≥ 7, no segment score < 2) and excellent (BBPS = 9) were among secondary endpoints.Results We randomized 300 inpatients (180 mobile) aged 71.7 ± 15.1 years in the intervention (49.7 %) and SOC (50.3 %) groups, respectively. Overall, more patients in the intervention group achieved adequate bowel preparation, but this difference did not reach statistical significance neither in the intention-to-treat [90/149 (60.4 %) vs. 82/151 (54.3 %); P = 0.29] nor in the per-protocol analysis [90/129 (69.8 %) vs. 82/132 (62.1 %); P = 0.19]. Overall BBPS score did not differ statistical significantly in the two groups, but the provision of specific verbal instructions was associated with significant higher rates of good (58.1 % vs. 43.2 %; P = 0.02) and excellent (31.8 % vs. 16.7 %; P = 0.004) bowel preparation compared to the SOC group. Administration of same-day bowel preparation and patient American Society of Anesthesiologists score > 2 were identified as risk factors for inadequate bowel preparation.Conclusions Provision of specific verbal instructions did not increase the rate of adequate bowel preparation in a population of mobilized and bedridden hospitalized patients.